The Space of Disgust. Materiality and Subalternity in Carolina Maria De Jesus (Itinera, 2025)
The concept of disgust is generally associated with the sensorial sphere of our body and is identified with a feeling of instinctive repulsion towards something that causes discom- fort. It has different meanings that emphasize its physical, ethical and social component. According to Darwin, disgust is one of the six primary sensations as it generates repul- sion, but for repulsion to occur as an immediate reaction, it must be re-symbolized through an interpretative action that occurs cognitively. Paraphrasing W. I. Miller (1997), disgust contributes to structure the world through the power of images and to internalize moral, collective and political attitudes. In this perspective, disgust is configured as a social catalyst, capable of creating isolated urban spaces of exclusion and marginality. In the novel Quarto de Despejo (1960) Carolina Maria de Jesus represents the existential conditions of a woman on the margins of society in a favela on the outskirts of São Paulo where she is forced to sell garbage to survive. The space of the favela is configured as a place of the marginalized, unwanted, victim of disgust by society. In the same way Caro- lina feels aversion towards São Paulo, which she defines as a «sick city», a symbol of exploitation, discrimination and violence. In the novel the physical element of garbage plays an important role and induces the protagonist to an act of internalization with which she projects the negative qualities of waste onto herself, in this way, she becomes the object and subject of disgust. Thus represented, disgust becomes a threat to one’s dignity, to the sense of belonging to a specific or abstract group, that is, to humanity. The language of the novel takes on forms of disgust in the representations of objects and waste that shape the surrounding space, which has now also become a theater of the repugnant. Car- olina Maria De Jesus more or less consciously consolidates her relationship with the ex- cluding space in which she moves by assuming the characteristics of the social marginalized.